2021
DOI: 10.3389/fphar.2021.656335
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Chemical Constituents, Clinical Applications, Pharmacology, Pharmacokinetics and Toxicology of Erigeron breviscapus

Abstract: Dengzhanxixin (DZXX), the dried whole plant of Erigeron breviscapus (Vaniot) Hand.-Mazz., belonging to Compositae and first published in Materia Medica of South Yunnan by Lan Mao in the Ming Dynasty (1368 AD–1644 AD), is included in Medicinal Materials and Decoction Pieces of the 2020 edition of the Pharmacopeia of the People’s Republic of China. Its main chemical components are flavonoids that mainly include flavonoid, flavonols, dihydroflavones, flavonol glycosides, flavonoid glycosides, coffee acyl compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 209 publications
0
14
0
Order By: Relevance
“…Flavonoids and flavonoid glycosides are abundant active components in E. breviscapus ( Wu et al, 2021 ). However, the regulatory mechanism underlying flavonoid and flavonoid glycoside metabolism remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flavonoids and flavonoid glycosides are abundant active components in E. breviscapus ( Wu et al, 2021 ). However, the regulatory mechanism underlying flavonoid and flavonoid glycoside metabolism remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Erigeron breviscapus ( E. breviscapus ) is a medicinal plant in the Compositae family with great medicinal potential, comprised of 25 kinds of flavonoids, 46 kinds of caffeoyl compounds, 78 kinds of volatile oils, and nearly 40 kinds of other compounds ( Wu et al, 2021 ). Previously, a total of 108 R2R3-MYB transcription factors have been identified in the E. breviscapus genome ( He et al, 2021 ; Song et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…EBHM accounts for more than 95% of the total resources in China and is becoming the main source of natural medicinal material in Yunnan Province. The therapeutic properties of EBHM include detoxification ( Mo et al, 2018 ), blood circulation activation ( Liu et al, 2021 ), channel and collateral activation ( Shi et al, 2015 ), inflammation reduction ( Zhu et al, 2018 ), and pain relief ( Wu et al, 2021 ). A variety of dosage forms, such as tablets, capsules, oral liquids, and injections, have been developed based on the different doses and delivery routes of EBHM extracts.…”
Section: Erigeron Breviscapus (Vant) Hand-mazzmentioning
confidence: 99%
“…Clinically, EBHM and its preparations are mainly used for the treatment of cardiovascular and cerebrovascular diseases and various types of inflammation. In recent years, studies have found that it has a good therapeutic effect on diabetes, kidney disease, glaucoma, liver damage and other diseases [ 17 ].…”
Section: Active Ingredients and Pharmacological Effects Of Ebhmmentioning
confidence: 99%
“…The major ingredient of commercially accessible preparations of EBHM is scutellarin, which is the glycosyloxyflavone with a molecular weight of 462.36 [ 17 , 19 ]. Scutellarin has been demonstrated to ameliorate cognitive impairment, anti-amyloid β-peptide (Aβ) toxicity, energy metabolism, suppress oxidative stress and neuroinflammation, stimulate astrocytes, increase the proliferation and differentiation of brain cells, and prevent apoptosis [ 20 ].…”
Section: Active Ingredients and Pharmacological Effects Of Ebhmmentioning
confidence: 99%